The appliance of macroprudential instruments to ease the financial distress caused by COVID-19: A global summary of the year 2020 - Hallamaa, Panu Matias (My University, 2021)
The COVID-19 has already been among us for nearly two years. It has caused significant humane despair but also caused substantial adverse shocks to the economy. There have been lockdowns, and supply chains have been under great stress. Even after vaccines have been developed against the disease, the uncertainty on the economy remains high. To provide more resilience for financial markets, governments have utilized macroprudential instruments. The instruments re-emerged in the aftermath of the Great Recession of 2007-2009 as regulators understood that it was not enough to supervise all the institutions individually. There is risk embedded directly in the financial markets, systemic risk, that can cause a significant downturn if left untouched. The systemic risk can be divided into two, cyclical and structural, depending on how it accumulates. Both are still divided further and followed by supervisors globally. Three global organizations, The Bank of International Settlements, International Monetary Fund, and Financial Stability Board, all have a crucial role in developing the macroprudential supervising. However, most of the decision-making happens at the domestic level, which, for example, provides Euro-countries way to balance unified monetary policy decisions. To spot the systemic risk from the markets, banking supervisors use an early warning system. It will inform of changes and enables the regulators to start acting well before the risk materializes. To address the specific macroprudential issue in the economy, the instruments divide into three categories. Credit-related instruments affect the demand side of lending, where liquidity-related and capital-related instruments do the same for supply. There is an issue with current research what comes to the macroprudential instruments. As the measurements re-emerged only after the last significant economic turmoil, there are primarily studies on how well they prevent a downturn. This thesis aims to understand better whether the active use of macroprudential instruments can hinder welfare loss during economic distress. To study this, data from 47 countries were researched and empirically tested using multiple linear regression. However, no statistically significant dependency concludes between the active utilization of macroprudential instruments and slighter loss of gross domestic product. The results do not mean that the instruments are not working. As they are just part of a more extensive repertoire of measurements, a more precise way to measure their effect should be found. Also, as their effect often takes place after a while, it might be that the empirical part of the thesis should be redone in the future.

Siitä on melkein kaksi vuotta, kun ensimmäiset Koronavirustartunnat raportoitiin. Siitä lähtien sillä on ollut valtavat humanitaariset sekä taloudelliset vaikutukset. Talouksia ympäri maailmaa on suljettu hetkellisesti, minkä takia negatiiviset shokit ovat olleet arkipäivää. Edes kehitetyt rokotteet eivät anna vielä varmuutta siitä, milloin pandemia loppuu. Parantaakseen talouksien kykyä kestää shokkeja valtiot ovat hyödyntäneet makrovakausmekanismeja. Kyseiset instrumentit olivat pitkään unohtuneita, mutta Euroalueen velkakriisi nosti ne takaisin valvojien mieliin. Makrovakausmekanismeja hyödynnetään järjestelmäriskin hallinnassa. Järjestelmäriski voidaan jakaa sykliseen ja rakenteellisen, riippuen siitä, mihin järjestelmän osiin riski on kerääntynyt. Useampi ylikansallinen organisaatio, kuten International Monetary Fund, tekee yhteistyötä kehittääkseen makrovakaudellista säätelyä. Säätelyä tapahtuu kolmella eri tasolla: kansainvälisellä, unioni- ja maakohtaisella tasolla. Havaitakseen järjestelmäriskejä markkinoilta on kehitetty ennakoivia systeemejä, jotka antavat lainsäätäjille mahdollisuuden toimia. Niiden perusteella määrätään makrovakausmekanismeja, jotka voidaan jakaa kolmeen osaan. Ne ovat luotonantoon, likviditeetiin ja pääomaan liittyvät instrumentit. Nykyisessä makrovakausmekanismeihin liittyvässä tutkimuksessa on ongelma. Se ei tällä hetkellä tarjoa tietoa siitä, kuinka hyvin instrumentit auttavat elvyttämään taloutta kriisissä. Se on sinänsä ymmärrettävää, sillä ne palasivat käyttöön viimeisimmän suuren finanssikriisin jälkeen. Pandemia kuitenkin tarjoaa meille mahdollisuuden tutkia asiaa siltä kantilta. Tutkielmassa tutkitaan 47 maan dataa hyödyntäen usean selittäjän lineaarista regressiota. Tavoitteena on selvittää, onko aktiivisesti makrovakausmekanismeja hyödyntäneet maat selvinneet paremmin pandemian aiheuttamista ongelmista kuin epäaktiiviset. Valitettavasti empiirinen tutkimus ei kykene löytämään tilastollisesti merkittävää riippuvuutta. Se ei kuitenkaan tarkoita, etteivätkö makrovakausmekanismit toimi. Täytyy löytää tulevaisuudessa toinen näkökulma tai tutkia niitä toisenlaisella metodilla. Makrovakausmekanismit vaikuttavat nimittäin usein viiveellä, joten on mahdollista, ettei niiden vaikutus siksi näy. Myös ne pitäisi määritellä selkeämmin, sillä tällä hetkellä määrittely vaihtelee huomattavasti lähteiden välillä. Jos ne nähtäisiin yleismaailmallisesti samalla tavalla, on varma, että niiden havainnointi muiden taloudellisten päätösten seasta helpottuisi.
Keywords: COVID-19; pandemics; macroeconomics; banking crises; economic regulation; fi=Taloustiede|en=Economics|; fi=Taloustieteen maisteriohjelma|en=Master's Programme in Economics|